Pre-Modern Bosom Serpents and Hippocrates' Epidemiae 5: 86: A Comparative and Contextual Folklore Approach - Davide Ermacora (Journal of Ethnology and Folkloristics)
A short Hippocratic passage (Epidemiae 5: 86) might constitute the earliest Western surviving variant of the well-known narrative and experiential theme of snakes or other animals getting into the human body (motif B784, tale-type ATU 285B*). This paper aims: 1) to throw light on this ancient passage through a comparative folkloric analysis and through a philological-contextual study, with reference to modern and contemporary interpretations; and 2) to offer an examination of previous scholarly enquiries on the fantastic intrusion of animals into the human body. In medieval and post-medieval folklore and medicine, sleeping out in the field was dangerous: snakes and similar animals could, it was believed, crawl into the sleeper’s body through the ears, eyes, mouth, nostrils, anus and vagina. Comparative material demonstrates, meanwhile, that the thirsty snake often entered the sleeper’s mouth because of its love of milk and wine. I will argue that while Epidemiae 5: 86 is modelled on this long-standing legendary pattern, for which many interesting literary pre-modern (and modern) parallels exist, its relatively precise historical and cultural framework can be efficiently analysed. The story is embedded in a broad set of Graeco-Roman ideas and practices surrounding ancient beliefs about snakes and attitudes to the drinking of unmixed wine.